(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
During the era of globalization, when the interaction of different languages and cultures increased, interest in studying the cultural-deterministic class of words such as realia increased. The word "realia" comes from the Latin adjective middle gender plural (realis, -e, mn. realia) and means" real "or" material". Linguists began to analyze reality as elements that reflect the national characteristics of society from the 50s of the last centuries. Thus, the review of theoretical work made it possible to determine whether scientists approach the problem of determining reality from different sides. Recall that we first consider reality from the point of view of culture and translation.